2013
DOI: 10.14742/ajet.452
|View full text |Cite
|
Sign up to set email alerts
|

"I'd be so much more comfortable posting anonymously": Identified versus anonymous participation in student discussion boards

Abstract: <span style="font-family: Times New Roman; font-size: small;"> </span><p>Academic staff members encourage university students to use online student discussion boards within learning management systems to ask and answer questions, share information and engage in discussion. We explore the impact of anonymity on student posting behaviour. An online survey was completed by 131 second year undergraduate psychology students (91% response rate). Overall, students reported being significantly more l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
27
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(31 citation statements)
references
References 29 publications
3
27
0
1
Order By: Relevance
“…The type of questions varied across the cohort and gave some indication of how the system was used to encourage interaction with staff. The use of the platform as a device for active disclosure of anxiety or misunderstanding is an interesting finding and confirms the results of Roberts and Rajah-Kanagasabai (2013), who suggested that students will make use of this facility if provided, and limited only by their self-efficacy. Krüger-Ross et al's (2013) discussion regarding overcoming the fear of publicly asking questions in class also appears to have been addressed, as well as Rothstein and Santana's (2011) consideration, that students who asked questions adopted a greater ownership of their learning.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…The type of questions varied across the cohort and gave some indication of how the system was used to encourage interaction with staff. The use of the platform as a device for active disclosure of anxiety or misunderstanding is an interesting finding and confirms the results of Roberts and Rajah-Kanagasabai (2013), who suggested that students will make use of this facility if provided, and limited only by their self-efficacy. Krüger-Ross et al's (2013) discussion regarding overcoming the fear of publicly asking questions in class also appears to have been addressed, as well as Rothstein and Santana's (2011) consideration, that students who asked questions adopted a greater ownership of their learning.…”
Section: Discussionsupporting
confidence: 80%
“…This may be an indication of the strength of the strict social norms governing behaviour in large cohorts as suggested by Ellison et al (2016), or as found by Savenski, Chou and Roy (2016), that a degree of self and community censorship exists even within these anonymous spaces. Alternatively, it could also imply that as suggested by Roberts and Rajah-Kanagasabai (2013) when exploring the use of anonymous discussion boards, that 'lack of trust' is still an issue.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In general, individuals who feel psychologically safe are more likely to perceive differences in opinions as opportunities rather than conflicts and to provide candid and critical peer feedback that can lead to higher quality learning outcomes (Lu and Bol 2007;van Gennip et al 2009). Moreover, the negative influences that self-consciousness can exert on the assessor in peer assessment activities can also be relieved (Roberts and Rajah-Kanagasabai 2013;Zhang et al 2010). With these liberating effects, anonymity can help relax the social customs and conventional roles that are usually expected of students (Miyazoe and Anderson 2011) and is thus preferable to a situation in which participants know each other (e.g., Hosack 2004).…”
Section: Anonymity As An Instructional Scaffold Within Peer Assessmentmentioning
confidence: 99%
“…This was discovered later when reviewing the answers to the survey. Research has already shown that students are often more comfortable when they are able to post anonymously (Roberts, 2013).…”
Section: Discussionmentioning
confidence: 99%